Influence of ceramic veneer on the transdentinal cytotoxicity, degree of conversion and bond strength of light-cured resin cements to dentin - Kitagawa, Fernanda Ali [UNESP]; Leite, Maria Luísa [UNESP]; Soares, Igor Paulino Mendes [UNESP]; Anselmi, Caroline [UNESP]; de Oliveira Ribeiro, Rafael Antônio [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Elsevier, 2022)
Objectives: To investigate the transdentinal cytotoxicity (TC), degree of conversion (DC), and micro shear bond strength (μSBS) to dentin of light-cured resin cements (LCRCs) photoactivated directly or through a ceramic veneer( ± CV). Materials and methods: The TC was assessed using human dentin discs adapted into artificial pulp chambers. Odontoblast-like cells were seeded on the pulp surface of the discs, then three LCRCs( ± CV) were applied on their etched and hybridized occlusal surface (n = 8/group). The adhesive systems of each LCRCs and sterile phosphate-buffered saline were used as positive and negative controls, respectively. After 24 h, the viability and morphology of cells adhered on discs were assessed. The extracts (culture medium + components of the materials diffused through the discs) were applied on the MDPC-23 to evaluate their viability, adhesion/spreading (A/S), alkaline phosphatase activity (ALP), and mineralized nodule formation (MN). LCRCs( ± CV) specimens were evaluated concerning the DC and μSBS to dentin. Data were analyzed by one-, two-, or three-way ANOVA/Dunnett, Sidak, and Games-Howell tests (α = 5%). Results: All LCRCs( ± CV) reduced cell viability, A/S, ALP, MN, and DC. Except for μSBS, the intensity of reduction was dependent on the LCRC used. LCRCs+CV resulted in lower DC and μSBS but did not increase the TC. Significance: Besides the presence of CV between the light source and LCRCs reduces the degree of conversion and bond strength to dentin, these materials cause variable level of transdentinal toxicity to pulp cells. Thus, the composition and curing protocols of LCRCs should be revisited and reinforced to prevent mechanical and biological drawbacks.
Keywords: Bond strength; Ceramic veneer; Cytotoxicity; Degree of conversion; Light–cured resin cement; Odontoblast